1997
DOI: 10.1046/j.1365-2672.1997.d01-400.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological stability and growth kinetics of Pseudomonas aeruginosa in bottled water

Abstract: Bacteriological stability of water bottled in plastic containers and the growth kinetics of Pseudomonas aeruginosa were determined. Samples of water from the source, water to be bottled, finished product and sterile water bottled in non‐returnable and returnable containers were analysed for aerobic colony count, coliforms, Escherichia coli and Ps. aeruginosa. The samples were examined for up to 30 d storage. Aerobic colony count increased 6 d after bottling to between 103 and 105 cfu ml−1. Coliforms and E. col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 2 publications
0
17
0
1
Order By: Relevance
“…The initial rapid growth seen with the A. hydrophila aroA strain after inoculation of nonsterilized water microcosms has also been reported for other A. hydrophila strains (10,18) as well as for other species, such as Vibrio vulnificus (11), Pseudomonas aeruginosa (35,69), and Photobacterium damselae subsp. damselae (21), and appears to be correlated with the water volume and the recipient surface (34).…”
Section: Discussionmentioning
confidence: 85%
“…The initial rapid growth seen with the A. hydrophila aroA strain after inoculation of nonsterilized water microcosms has also been reported for other A. hydrophila strains (10,18) as well as for other species, such as Vibrio vulnificus (11), Pseudomonas aeruginosa (35,69), and Photobacterium damselae subsp. damselae (21), and appears to be correlated with the water volume and the recipient surface (34).…”
Section: Discussionmentioning
confidence: 85%
“…14 The pasteurization will, however, greatly affect the microbial load and composition of the carrot juice. The differences in both the microbial biota and in the substrate will affect the maximal growth rate, since the doubling time for some species is greatly influenced by competition from accompanying flora 15,16 and the composition of the medium. 17 -19 Growth rates similar to ours have, however, been found for a vegetable salad containing red cabbage, lettuce and carrot.…”
Section: Results and Discussion Microbial Growthmentioning
confidence: 99%
“…The presence of HPC did not favour the establishment and maintenance of culturability of C. jejuni. The fact that C. jejuni did not survive either in sterile water (data not shown) demonstrated that C. jejuni mortality in bottled water was not due to competition or any antagonistic activity of HPC cells although this latter characteristic has been them assigned (Tamagnini and Gonzalez, 1997;Vachee et al, 1997). However Tatchou …”
Section: Influence Of Heterotrophic Flora On C Jejuni Survivalmentioning
confidence: 96%